Being for others : critical reflections on the stranger, the estranged and the self in participatory art,Ineffaceable - Munro, Samantha Fawn (Rhodes University, Faculty of Humanities, Department of Fine Art, 2015)
By referring to established concepts and theories which contemplate our experiences in relation to others and space, this thesis examines the interactions and responses of an audience during various participatory artworks. I draw upon Jean-Paul Sartre's Being and Nothingness and Elizabeth Grosz' Architecture From The Outside: Essays on Virtual and Real Space in order to understand our interactions with other people, our interactions inside an environment, and the objects and ceremonies we use during these interactions. I align these experiences with the methods which are employed to anticipate and create the interactions between an audience and a participatory artwork. Our daily interactions can be considered a frame that an artist shapes for their represented situation to allow, provide and guide an audience towards their possibilities for movements and actions within a participatory artwork. The interactions that occur in participatory art are done in relation to others and include groups of people interacting with each other rather than an individual disembodied experience. I refer to Claire Bishop in her book, Artificial Hells, and Nicolas Bourriaud in Relational Aesthetics in order to define participatory art. In defining participatory art I focus on the idea that participation is a social activity without which the artwork does not function or exist. I unravel Brett Bailey's Exhibit A, Anthea Moys Anthea Moys vs The City of Grahamstown and Christian Boltanski's Personnes in terms of the frame they use to construct participation and interaction. I refer to my own exhibition Ineffaceable as an exploration of these frames which encourage participation. The inside and the outside are a constant theme throughout this thesis and my exhibition. This thematic re-emerges in relation to a number of opposing and fluctuating dynamics: the self and the other; the object and the subject; familiarity and strangeness; the participator and the spectator; the immersive and the disembodied; and the artwork and the audience. Participatory art has not been sufficiently explored particularly in South Africa with South African case studies and particularly from a practical standpoint that includes methodologies for creating participation. This thesis hopes to enrich and contribute to the contemplations on participatory art by focusing on our interactions with others.
Keywords: Self; Identity (Philosophical concept) in art; Alienation (Philosophy); Interactive art; Art appreciation; Art exhibition audiences; Interactive art -- Themes, motives; Social interaction